Measuring the performance of contractors in government construction projects in developing countries: Uganda’s context - Benon C. Basheka; Milton Tumutegyereize (African Journal of Environmental Economics and Management, 2013)
Traditionally, the success of projects is measured on time, cost and quality parameters; although, most construction projects in Uganda have not performed well on each of these parameters. In this paper, we identify important indicators that are useful for measuring contractors’ performance in Uganda’s context. The paper develops a simple performance measurement framework for measuring performance of contractors. It also identifies a set of challenges faced by contractors in Uganda that need the attention of policy makers and those in managerial positions. The findings are original and add to the stock of existing knowledge in understanding the unique context of the construction industry in developing countries.